A prospective marker for the prediction of postoperative deep venous thrombosis: Neutrophil extracellular traps - Li, Yin; Jiang, Qinyi; Zhou, Xiaohua; Wu, Mengyuan; Chen, Jian; Liu, Hao; Dai, Siming; Zheng, Ziyang; Zhao, Xuan; Zhang, Chenxi; Shi, Zhuoying; Zhang, Haitao; et al. (Frontiers in Cell and Developmental Biology, 2022)
Deep venous thrombosis (DVT) is a common medical complication in patients with lumbar fractures. The current study aimed to investigate the predictive value of neutrophil extracellular traps (NETs) in postoperative DVT formation in patients with lumbar fractures and to develop a nomogram relating clinical admission information for prediction. Patients who underwent open reduction and pedicle screw internal fixation in the treatment of single-segment lumbar fracture in the Department of Spine Surgery, the First Affiliated Hospital of Nanjing Medical University, from December 2020 to June 2022 were enrolled in this study. Baseline data and laboratory results were collected from enrollees, and the primary study endpoint event was the occurrence of DVT in patients after surgery. Multivariable logistic regression analysis was used to identify risk factors associated with higher odds of DVT after surgery. A nomogram was constructed using the results of the multivariable model. The calibration plot and receiver operating characteristics (ROC) curve were used to show the satisfactory predictive capacity of the model. Of these 393 patients who did not have DVT preoperatively, 79 patients developed it postoperatively, and 314 did not, respectively. Multivariate analysis showed that higher body mass index (BMI) (BMI between 24 and 28: RR = 1.661, 95% CI = 0.891–3.094; BMI ≤28: RR = 5.625, 95% CI = 2.590–12.217; reference: BMI <24), neutrophils (RR = 1.157, 95% CI 1.042–1.285), D-dimer (RR = 1.098, 95% CI 1.000–1.206), and citrullinated histone H3 (CitH3) (RR = 1.043, 95% CI 1.026–1.060) were independent risk factors for postoperative DVT. Using the multivariable analysis, we then constructed a nomogram to predict DVT, which was found to have an area under the curve of 0.757 (95% CI = 0.693–0.820). Calibration plots also showed the satisfied discrimination and calibration of the nomogram. In conclusion, patients with lumbar fractures with postoperative DVT had higher levels of NETs in the circulation preoperatively compared to those without postoperative DVT. Furthermore, based on BMI, D-dimer, neutrophils, and CitH3, we developed a predictive model to predict postoperative DVT incidence in these patients.